TRADISI TOLAK BALAK DI AIR TERJUN SEDUDO DI DESA NGILMAN KECAMATAN SAWAHAN KABUPATEN NGANJUK - Ellen Marita Andiana; Novita Wahyuningsih (Haluan Sastra Budaya, 2020)
Sedudo Waterfall Tradition is a ceremony that has passed from ancient times until now, the culture of Siraman since the Majapahit era and the glory of Islam in Java Island, is often used to bathe the weapons of the heirlooms of the former kingdom. Relic of Indonesian culture still preserved by government and society in Ngilman Village, Sawahan Sub-District, Nganjuk Regency, East Java. In this tradition of balustrade various ceremonial traditions, better known as Siraman Sedudo Waterfall. This objection is aimed at 1) the happiness of selametan in one suro, 2) including the procession of the anniversary of Nganjuk, 3) showing the handicrafts, Javanese art and introducing Sedudo Waterfall tour in Ngilman Village, Sawahan Sub-District, Nganjuk Regency, and showing among other people in the region. The benefit is to increase the regional income of the Ngilman community in the Nganjuk regency. With the processions at this event, the many stages that must first pass the gambyong dance performances are six female dancers, then to take twelve to get water with twelve pejakas. After completing the tradition of chopping girls and pejaka begin to enter the sedudo waterfall that has been prepared to take the water fell from the top, just under the waterfall and bring the water in the kendil directly to the big pot, to be stored and enshrined in Pendopo Kabupaten Nganjuk.Semua done in the procession there is a meaning of its own.